Hierarchical Capillary Coating to Biofunctionlize Drug-Eluting Stent for Improving Endothelium Regeneration - Jing Wang; Yunfan Xue; Jun Liu; Mi Hu; He Zhang; Kefeng Ren; Yunbing Wang; Jian Ji (Research, 2020)
The drug-eluting stent (DES) has become one of the most successful and important medical devices for coronary heart disease, but yet suffers from insufficient endothelial cell (EC) growth and intima repair, eventually leading to treatment failure. Although biomacromolecules such as vascular endothelial growth factor (VEGF) would be promising to promote the intima regeneration, combining hydrophilic and vulnerable biomacromolecules with hydrophobic drugs as well as preserving the bioactivity after harsh treatments pose a huge challenge. Here, we report on a design of hierarchical capillary coating, which composes a base solid region and a top microporous region for incorporating rapamycin and VEGF, respectively. The top spongy region can guarantee the efficient, safe, and controllable loading of VEGF up to 1 μg/cm2 in 1 minute, providing a distinctive real-time loading capacity for saving the bioactivity. Based on this, we demonstrate that our rapamycin-VEGF hierarchical coating impressively promoted the competitive growth of endothelial cells over smooth muscle cells (ratio of EC/SMC~25) while relieving the adverse impact of rapamycin to ECs. We further conducted the real-time loading of VEGF on stents and demonstrate that the hierarchical combination of rapamycin and VEGF showed remarkable endothelium regeneration while maintaining a very low level of in-stent restenosis. This work paves an avenue for the combination of both hydrophobic and hydrophilic functional molecules, which should benefit the next generation of DES and may extend applications to diversified combination medical devices.